The effect of antibiotics on the intestinal microbiota in children - a systematic review - Wurm, Juliane; Curtis, Nigel; Zimmermann, Petra (Frontiers in Allergy, 2024)
BackgroundChildren are the age group with the highest exposure to antibiotics (ABX). ABX treatment changes the composition of the intestinal microbiota. The first few years of life are crucial for the establishment of a healthy microbiota and consequently, disturbance of the microbiota during this critical period may have far-reaching consequences. In this review, we summarise studies that have investigated the effect of ABX on the composition of the intestinal microbiota in children.MethodsAccording to the PRISMA guidelines, a systematic search was done using MEDLINE and Embase to identify original studies that have investigated the effect of systemic ABX on the composition of the intestinal microbiota in children.ResultsWe identified 89 studies investigating a total of 9,712 children (including 4,574 controls) and 14,845 samples. All ABX investigated resulted in a reduction in alpha diversity, either when comparing samples before and after ABX or children with ABX and controls. Following treatment with penicillins, the decrease in alpha diversity persisted for up to 6–12 months and with macrolides, up to the latest follow-up at 12–24 months. After ABX in the neonatal period, a decrease in alpha diversity was still found at 36 months. Treatment with penicillins, penicillins plus gentamicin, cephalosporins, carbapenems, macrolides, and aminoglycosides, but not trimethoprim/sulfamethoxazole, was associated with decreased abundances of beneficial bacteria including Actinobacteria, Bifidobacteriales, Bifidobacteriaceae, and/or Bifidobacterium, and Lactobacillus. The direction of change in the abundance of Enterobacteriaceae varied with ABX classes, but an increase in Enterobacteriaceae other than Escherichia coli was frequently observed.ConclusionABX have profound effects on the intestinal microbiota of children, with notable differences between ABX classes. Macrolides have the most substantial impact while trimethoprim/sulfamethoxazole has the least pronounced effect.